Studies in medieval Jewish intellectual and social history festschrift in honor of Robert Chazan - Chazan, Robert; Wolfson, Elliot R.; Schiffman, Lawrence H.; Engel, David (Leiden ; Boston : BRILL, 2012)
Thirteen leading scholars offer a fresh look at four key topics in medieval Jewish studies: the history of Jewish communities in Western Christendom, Jewish-Christian interactions in medieval Europe, medieval Jewish Biblical exegesis and religious literature, and historical representations of medieval Jewry.
Robert Chazan: in appreciation and friendship -- Guibert of Nogent and William of Flay and the problem of Jewish conversion at the time of the First Crusade -- Rashi's choice: the Humash commentary as rewritten Midrash -- The commentary of Rashi on Isaiah and the Jewish-Christian debate -- Were Jews made in the image of god? Christian perspectives and Jewish existence in Medieval Europe -- Jewish knowledge of Christianity in the twelfth and thirteenth centuries -- Dreams as a determinant of Jewish law and practice in Northern Europe during the High Middle Ages -- Orality and literacy: the French Tosaphists -- Torah and the Messianic Age: the polemical and exegetical history of a rabbinic text -- Textual flesh, incarnation, and the imaginal body: Abraham Abulafia's polemic with Christianity -- The Jewish cemeteries of France after the expulsion of 1306 -- The cruel Jewish father: from miracle to murder -- From Solomon Bar Samson to Solomon ibn Verga: tales and ideas of Jewish martyrdom in Shevet Yehudah -- Salo Baron's view of the Middle Ages in Jewish history: early sources -- Bibliography of the works of Robert Chazan.
Includes bibliographical references.
Description based on print version record.
Keywords: Jews -- Europe -- History -- To 1500.; Christianity and other religions -- Judaism -- History; Judaism -- Relations -- Christianity -- History; Europe -- Ethnic relations -- History -- To 1500.; Rashi, -- 1040-1105.; Tosafists; Martyrdom -- Judaism; Jewish law; Christianity and other religions -- Judaism -- History; Europe -- Ethnic relations -- History -- To 1500.; Jewish law; Jews -- Europe -- History -- To 1500.; Judaism -- Relations -- Christianity -- History; Martyrdom -- Judaism; Rashi, 1040-1105. Perush Rashi?al ha-Torah.; Tosafists; Religion; RELIGION / Judaism / History; Electronic books